Replacing oxygen evolution reaction in water splitting process by electrochemical energy-efficient production of high-added value chemicals with co-generation of green hydrogen - L. Oliveira, Herbet; Santos, José E.L.; Gondim, Amanda D.; Cavalcanti, Livia N.; Correia de Carvalho, Fabíola; Castro, Suely S.L.; Martínez-Huitle, Carlos A. [UNESP]; dos Santos, Elisama V. [UNESP] (Elsevier, 2024)
The utilization of biomass represents a promising alternative to the use of fossil fuels in facing both the energy problem and environmental pollution. Using the electrochemical oxidation of organic pollutants instead of the oxygen evolution reaction at the anode and the hydrogen evolution reaction at the cathode of an electrolyzer, it is possible to make high-value chemicals, break down pollutants, and produce hydrogen efficiently at the same time. In this study, the scale-up of the electrochemical treatment was investigated by treating technical cashew nutshell liquid effluent using a photovoltaic-driven electrochemical reactor with two compartments and equipped with a boron-doped diamond electrode as the anode and a Ni stainless-steel mesh as the cathode. Tests were carried out varying the anode current densities (40, 70, and 100 mA cm-2), the nature of the electrolyte solution (NaOH and Na2SO4), and the concentration of technical cashew nutshell liquid (0.01, 0.05, or 0.10 %). The results clearly shown that it is possible to successfully scale up a divided electrochemical reactor (passing from the batch approach of previous works to the flow approach of this study), favoring a selective accumulation of acetate (600 mg L-1) in the anodic compartment. In addition, the simultaneous production of green hydrogen (0.182 L h-1) was achieved when electrolyzing a biomass effluent containing 0.10 % technical cashew nutshell liquid in 1 mol L-1 NaOH and applying a current density of 40 mA cm-2. In conclusion, the sustainable electrochemical transformation of the waste (from technical cashew nutshell liquid into valuable products and energy carriers) was successfully achieved. We believe that the results will help the energy transition towards zero carbon emission and a cost-effective production of hydrogen through an integrated-hybrid process.
Keywords: Biomass exploitation; Carboxylates; Design strategies; Diamond electrode; Electro-refinery; Energy efficiency; Green hydrogen